Chemical composition of essential oil from some species of Asarum L. genus in Vietnam - Thai, Tran Huy; Hien, Nguyen Thi; Hoi, Tran Minh; Tuan, Nguyen Anh; Dat, Nguyen Tien; Hai, Nguyen Thi (Academia Journal of Biology, 2013)
Esential oil yield from Asarum balancae leaves, roots and stems was 0.02% (by air dry material). Essential oil was analyzed by GC/MS and 18 components of esential oil were identified. Major component were elemicine (71.53%) and trans isoelemicine (19.85%). Esential oil yield from Asarum yunnanense leaves, stem and roots was 0.16% (by air dry material). Essential oil was analyzed by GC/MS and 33 components of esential oil were identified. Major component were E-methyl isoeugenol (47.39%), Cis-β-elemene (5.94%), bicyclogermacrene (4.58%), Myristicine (4.26%) and δ-elemene (4.90%). Esential oil yield from Asarum petelotii leaves, stem and roots was 0.002% (by air dry material). Essential oil was analyzed by GC/MS and 25 components of esential oil were identified. Major component were myristicine (59.06%) and dilapiole (17.67%). Esential oil yield from Asarum cordifolium leaves, roots and stems was 0.22% (by air dry material). Essential oil was analyzed by GC/MS and 26 components of esential oil were identified. Major component were elemicine (84.38%) and methyl eugenol (3.63%).